Beyond the Great War: Making Peace in a Disordered World - Bouchard, Carl; Ingram, Norman (University of Toronto Press, 2022)
Following the end of the First World War, a new world order emerged from the Paris Peace Conference of 1919. It was an order riddled with contradictions and problems that were only finally resolved after the Second World War. Beyond the Great War brings together a group of both well-established and younger historians who share a rejection of the dominant view of the peace process that ended the First World War. The book expands beyond the traditional focus on diplomatic and high political history to question the assumption that the Paris Peace Treaties were the progenitors of a new world order. Extending the ongoing debate about the success of the Treaty of Versailles and surrounding events, this collection approaches the heritage of the Great War through a variety of lenses: gender, race, the high politics of diplomacy, the peace movement, provision for veterans, international science, socialism, and the way the war ended. Collectively, contributors argue that the treaties were at best a mitigated success, and that the "brave new world" of 1919 cannot be separated from the Great War that preceded it.

“No Women of the World Hate War and Seek Peace More than the Colored Women”: Mary Church Terrell’s Bid for Racial Justice and Women’s Rights in 1919: making peace in a disordered world - Siegel, Mona; Ingram, Norman; Bouchard, Carl (Beyond the Great War: Making Peace in a Disordered World, 2022)
"Was the end of the First World War a catalyst for progress or the harbinger of future conflict? The essays in this collection address the impact of the end of the First World War, with a focus on the extent to which the end of the war and the Paris peace process encouraged or disrupted the nascent international order. The focus is on western Europe, particularly France. Among the topics addressed are the relationship between gender and peace activism, international and trans-Atlantic connections, and the significance of French domestic politics to international relations. Collectively, the essays extend the ongoing debate about the success of the Treaty of Versailles: they add nuance to the debate by showing how particular issues combined both success and failure. The volume should be of interest to military, diplomatic, and international historians, with particular chapters of interest to a wider range of scholars in European history.